2000
DOI: 10.1007/s005950070121
|View full text |Cite
|
Sign up to set email alerts
|

Multiple inflammatory pseudotumors mimicking liver metastasis from colon cancer: Report of a case

Abstract: A 54-year-old man underwent an operation for colon cancer histologically diagnosed as moderately differentiated adenocarcinoma with clinical staging of Dukes C. He was prescribed carmofur for adjuvant chemotherapy. A follow-up computed tomography scan done 6 months later revealed two new low-density areas in the liver. A diagnosis of metastatic adenocarcinoma from the previous colon cancer was presumed, based on the patient's history and radiological findings, and resection of the affected area of liver was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…Sakai et al 16 reported on a series of five patients with IPT. CT appearances were of low-density lesions with irregular delayed enhancement as also described by other authors 4,12,16,18,19 . Seki et al 20 , demonstrated peripheral enhancement of IPT in the early phases of dynamic CT in three patients.…”
Section: Radiologysupporting
confidence: 72%
“…Sakai et al 16 reported on a series of five patients with IPT. CT appearances were of low-density lesions with irregular delayed enhancement as also described by other authors 4,12,16,18,19 . Seki et al 20 , demonstrated peripheral enhancement of IPT in the early phases of dynamic CT in three patients.…”
Section: Radiologysupporting
confidence: 72%
“…Some IPT of the liver have been associated with malignant tumors. In the English-language literature, 6 such cases have been reported [1,7,8,11,13,16] and 4 such cases in the Japanese-language literature [9]. The clinical findings of 10 reported cases and the present 2 cases are summarized in Table 1; 11 cases were reported from Japan and 1 from the United Kingdom.…”
Section: Discussionmentioning
confidence: 81%
“…In cases 6 and 10, a cystic space was detected in the lesions of the liver, and Staphylococcus aureus was cultured from the cystic fluid in both cases. Obliterating phlebitis was found Ishida et al [7] Saito et al [13] Akiyama et al [1] Kobayashi et al [9] Yokoyama et al [9] Nakamura et al [9] Isobe et al [8] Tajima et al [16] Newbould et al [11] a Cancer stage is classified using TNM Classification of Malignant Tumors (Sixth Edition) from the International Union Against Cancer in case 3 [9] and our present cases (cases 1 and 2). Therefore, the etiology of hepatic IPT may be similar to that of the pyogenic liver abscess because of the similarity of associated cancer types and the etiological correlation of clinical course in some patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations